A Study on Separation Efficiency of Multiphase Desander - Arwinder Singh, Jigiri Singh; Muhammad Izzat Nor, Ma'arof; Kavenraj, Rajendran; Girma, Tadesse Chala (INTI International University, 2022)
Drilling process in the oil and gas industry will commonly result in large amounts of solids (typically sand and small stones) to make its way into the pipeline. In overcoming this predicament and to prolong the life of the processing machineries, a desander is used. However, a large desander usually results in higher cut point where the smaller particles are not efficiently removed, reducing its separation efficiency. The study was aimed to develop a 12” desander or better known as a hydrocyclone that is able to have a high separation efficiency. The hydrocyclone is designed to handle high throughputs of a 12” desander but is able to achieve lower cutpoints and efficiency equivalent to a smaller hydrocyclone if not better. The geometry of the hydrocyclone was designed based on the optimal configuration for 12” hydrocyclone while manipulating the vortex finder to total length ratio ranging from 0.1 to 0.5. The 3D geometry was developed in ANSYS Space Claim then was proceeded to ANSYS Fluent for carrying out Computational Fluid Dynamics (CFD) Simulation. The hydrocyclone was subjected to a fixed feed pressure of 20 Psi to obtain the optimal design. Upon obtaining the optimal design, the hydrocyclone was subjected to varying feed pressure from 15 to 35 Psi with fixed intervals of 5 Psi. Conclusively, the hydrocyclone with 0.1 vortex finder ratio was found to result in the highest separation efficiency and the hydrocyclone operating at 25 Psi was found to further increase in the separation efficiency. However, this research has a gap in terms of the performance of the other designs at various feed pressures and has a lack of data in terms of cutpoint.